Outcomes of membranous and proliferative lupus nephritis – analysis of a single-centre cohort with more than 30 years of follow-up. (17th April 2020) - Farinha, Filipa; Pepper, Ruth J; Oliveira, Daniel G; McDonnell, Thomas; Isenberg, David A; Rahman, Anisur
Abstract: Objectives: To compare membranous lupus nephritis (MLN) and proliferative lupus nephritis (PLN) with respect to survival, demographic, clinical and laboratory characteristics; and to investigate predictors of renal and patient survival. Methods: Single-centre retrospective observational study. Patients with biopsy-proven PLN, MLN and mixed lupus nephritis were included. Groups were compared using appropriate statistical tests and survival was analysed through the Kaplan-Meier method. Cox regression analysis was performed to investigate predictors of renal and patient survival. Results: A total of 187 patients with biopsy-proven lupus nephritis (135 with PLN, 38 with MLN and 14 with mixed LN) were followed for up to 42 years (median 12 years). There was a higher proportion of MLN amongst Afro-Caribbeans than amongst Caucasians (31% vs 15%, P = 0.010). Patients with MLN had significantly lower anti-dsDNA antibodies ( P = 0.001) and higher C3 levels ( P = 0.018) at diagnosis. Cumulative renal survival rates at 5, 10, 15 and 20 years were 91, 81, 75 and 66% for PLN and 100, 97, 92 and 84% for MLN, respectively ( P = 0.028). Cumulative patient survival at 5, 10, 15 and 20 years was 94, 86, 80 and 76%, with no difference between PLN and MLN. Urinary protein-creatinine ratio above 42 mg/mmol and eGFR below 76 ml/min/1.73 m 2, one year after the diagnosis of LN, were the strongest predictors of progression to end-stage renal disease. eGFR below 77 ml/min/1.73 m 2, at one year, development of end-stage renal disease and Afro-Caribbean ethnicity were associated with higher mortality. Conclusion: Patients with MLN and PLN differ significantly regarding serological profiles and renal survival, suggesting different pathogenesis. Renal function at year one predicts renal and patient survival.